RNF8 promotes efficient DSB repair by inhibiting the pro‐apoptotic activity of p53 through regulating the function of Tip60. (7th February 2020) - Chen, Hongyu; Shan, Jin; Liu, Jialing; Feng, Yunpeng; Ke, Yueshuang; Qi, Wenjing; Liu, Wenguang; Zeng, Xianlu
Abstract: Objectives: RING finger protein 8 (RNF8) is an E3 ligase that plays an essential role in DSB repair. p53 is a well‐established tumour suppressor and cellular gatekeeper of genome stability. This study aimed at investigating the functional correlations between RNF8 and p53 in DSB damage repair. Materials and methods: In this article, wild‐type, knockout and shRNA‐depleted HCT116 and U2OS cells were stressed, and the roles of RNF8 and p53 were examined. RT‐PCR and Western blot were utilized to investigate the expression of related genes in damaged cells. Cell proliferation, apoptosis and neutral cell comet assays were applied to determine the effects of DSB damage on differently treated cells. DR‐GFP, EJ5‐GFP and LacI‐LacO targeting systems, flow cytometry, mass spectrometry, IP, IF, GST pull‐down assay were used to explore the molecular mechanism of RNF8 and p53 in DSB damage repair. Results: We found that RNF8 knockdown increased cellular sensitivity to DSB damage and decreased cell proliferation, which was correlated with high expression of the p53 gene. RNF8 improved the efficiency of DSB repair by inhibiting the pro‐apoptotic function of p53. We also found that RNF8 restrains cell apoptosis by inhibiting over‐activation of ATM and subsequently reducing p53 acetylation at K120 through regulating Tip60. Conclusions: Taken together, these findings suggested that RNF8 promotes efficient DSB repair by inhibiting the pro‐apoptotic activity of p53 through regulating the function of Tip60.